Learning in Troubled Times: Parents’ Perspectives on Emergency Remote Teaching and Learning - Seabra, Filipa (2021)
The COVID-19 pandemic triggered profound social consequences, affecting all aspects of human activity, including education. The process of remote teaching that was implemented in response to this crisis is known as emergency remote teaching and learning (ERTL). The present study focuses on Portuguese parents’ perspectives about this process. Data were gathered through an online questionnaire, answered by 203 parents of preschool, basic, and secondary education students (ages 3–18), focusing on self-perceived digital competence, satisfaction with ERTL, and pedagogical activities developed with their children. Parents were moderately satisfied with ERTL but expressed a marked increase in their workload, particularly those working from home. Parents of children in the second cycle of basic education (ages 10–12) were less satisfied with the process. A variety of activities was promoted, responding to different educational levels’ characteristics. Results show the importance of promoting parents’ digital competence and directing support policies, particularly to parents of younger children (ages 3–12), and raise concerns about equity. © 2021 by the authors. Licensee MDPI, Basel, Switzerland.